Reproduction and winter biology of polar cod Boreogadus saida from Svalbard waters - Korshunova, Ekaterina (Universitetet i Tromsø, 2012)
Polar cod (Boreogadus saida) is considered to be a key species in the Arctic marine ecosystems. Yet detailed or even basic knowledge regarding its biology and adaptations, especially during the polar night, are in many cases poor. No field data is presently available on the gonad development of polar cod, its reproductive biology and associated bioenergetics. Accordingly, polar cod was sampled at different locations in Svalbard waters in August, September, November and January. Gonadosomatic index (GSI) and hepatosomatic (HSI) indices were calculated as indicators of the physiological state of the fish. Maturity stages were determined by microscopic histological techniques. Energy reserves (total lipids, proteins and carbohydrates) were quantified in liver and gonads as well as cellular respiration through Electron Transport System (ETS) activity. Results indicated that polar cod prepared for spawning and started developing their gonads in August and September. The fish with GSI≥4% were considered mature as they had spawned at least once or were preparing for their first spawning. A general increase in GSI was observed together with a general increase in the total energy content in polar cod gonads from August to January. Males showed fully developed gonads in November, i.e. two months earlier than females. HSI and total energy content in liver tended to be constant over time, except for males where HSI was lower in January compared to the other months. Furthermore, only mature males showed a negative correlation between GSI and HSI that indicated a drain of energy from liver to gonads in males. It was hypothesized that female and male polar cod had different reproductive strategies. Based on histological analysis of the gonads, female polar cod were confirmed to be iteroparous and to be able to spawn more than once in their lifetime. Indeed, the presence of post-ovulatory follicles in the ovaries of mature females in August indicated that the fish had spawned the previous winter, while the progressive oocytes ...